IMPACT OF CUSTOMER LOYALTY IN MEDIATING OF INTRINSIC AND EXTRINSIC ATTRIBUTES QUALITY OF PURCHASE INTENTION - Albari .; Sofian Dewi (Journal of Management and Business, 2016)
A business organization should always strive to maintain its sustainability by creating loyalty and purchase intention towards its products. The activity is specifically required for an organization engaged in the restaurant industry. The organization needs to be aware of which product attributes are in concern to the customers when purchasing the food in a restaurant. This research was intended to measure the importance of the quality from intrinsic and extrinsic attributes of a product for the customers and its impact on the customers’ loyalty and purchase intention. The research was conducted by involving the customers of a pizza product in Yogyakarta. 116 respondents were selected using convenience sampling technique. Meanwhile, the data being obtained were analyzed by using structural equation modeling (SEM) approach and data processing program named AMOS 20.0 after going through two stages of testing, namely data validity and data reliability tests. The results showed that the intrinsic attributes quality has a direct and positive impact on the customer’s purchase intention, but there is no impact  on their loyalty. On the other hand, the extrinsic attributes quality has both direct and indirect impacts on the purchase intention through the loyalty mediator variable. The results also demonstrated the dominance of the importance of loyalty in the research model. This was indicated by the significance of direct impact or predictive total impact of loyalty towards purchase intention as compared to the impact of intrinsic and extrinsic attributes quality.